Changes in attitudes towards professionalism among medical students during clinical clerkship - Abu, Cherry T.
Professionalism is a core competency of physicians, identified as a learning outcome in international and local statements of educational aims for the Doctor of Medicine program. In all the efforts geared towards supporting students develop high standards of professionalism through the 4-year course of medical education, perhaps the greatest gap is in its assessment. This study tracked changes in attitudes towards professionalism in terms of the six elements of professionalism identified by the American Board of Internal Medicine (ABIM) including altruism, accountability, excellence, duty, honor and integrity, and respect for others among medical students during clinical clerkship. The study aimed to determine 1) how attitudes towards professionalism among medical students change during clinical clerkship rotations; 2) which specific attitudes towards professionalism change as they go through different clinical rotations; and 3) if there are associations between changes in attitudes towards professionalism and some demographic factors and specific clinical rotations. This is a cohort study with a baseline and three consecutive clinical rotation measurements of attitudes towards professionalism among fourth year students in a medical school accredited as Level 3 by the Philippine Accrediting Association of Schools, Colleges and Universities (PAASCU) as they rotated in the different clinical departments for the first semester of academic year (AY) 2018-2019. A 36-item questionnaire based on the validated Penn State Questionnaire on Professionalism (PSQP) was used. Data were analyzed using the Statistical Package for the Social Sciences Software Version 25. Frequency counts, means, percentages, t-tests and paired t-tests, analysis of variance and chi-square were used to analyze the data. Results and discussion: The attitudes towards professionalism among medical students were positive and stable through several measurements but did not significantly improve over time. The scores were highest and most stable for altruism, excellence, and honor and integrity. No significant association was found between any change in attitudes and demographic factors including age, gender, and pre-medical course or any specific clinical rotation. Conclusion: The positive attitudes towards professionalism among medical students in a PAASCU-accredited Level 3 medical school for the first semester of AY 2018-2019 did not change significantly from baseline to three consecutive clinical rotations. No association was found between attitude change and the medical student's age, gender, pre-medical course and specific clinical rotations.